2018
DOI: 10.1098/rspb.2018.1681
|View full text |Cite
|
Sign up to set email alerts
|

Control of seminal fluid protein expression via regulatory hubs in Drosophila melanogaster

Abstract: Highly precise, yet flexible and responsive coordination of expression across groups of genes underpins the integrity of many vital functions. However, our understanding of gene regulatory networks (GRNs) is often hampered by the lack of experimentally tractable systems, by significant computational challenges derived from the large number of genes involved or from difficulties in the accurate identification and characterization of gene interactions. Here we used a tractable experimental system in which to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…When considering all SFP genes, M males showed on average 16.6% lower expression than P males. The breadth of this reduced investment in SFP gene expression in M males (113 of the 132 SFP genes show nominally lower expression) is consistent with the idea that these genes are tightly coregulated (81) and suggests that fine-tuned tailoring of the composition of the ejaculate may be to some extent evolutionarily constrained. The reduced investment in SFP gene expression in M males was confirmed by qPCR analyses for the five most well-characterized SFP genes ( Acp26Aa , Acp29AB , Acp36DE , Acp62F , and SP ) across an extended time course spanning the first 5 d post eclosion ( SI Appendix , Fig.…”
Section: Resultssupporting
confidence: 75%
“…When considering all SFP genes, M males showed on average 16.6% lower expression than P males. The breadth of this reduced investment in SFP gene expression in M males (113 of the 132 SFP genes show nominally lower expression) is consistent with the idea that these genes are tightly coregulated (81) and suggests that fine-tuned tailoring of the composition of the ejaculate may be to some extent evolutionarily constrained. The reduced investment in SFP gene expression in M males was confirmed by qPCR analyses for the five most well-characterized SFP genes ( Acp26Aa , Acp29AB , Acp36DE , Acp62F , and SP ) across an extended time course spanning the first 5 d post eclosion ( SI Appendix , Fig.…”
Section: Resultssupporting
confidence: 75%
“…We also sought to understand the regulatory differences that underlie between-SFP variation in sensitivity to competition. Recent work has shown that groups of SFPs share putative binding sites for particular miRNAs (53). Thus, it may be that specific miRNAs are responsible for driving the changes in SFP expression that facilitate strategic changes in ejaculate composition.…”
Section: Resultsmentioning
confidence: 99%
“…Sfp gene expression can also change: reduced RNA levels of ovulin and Acp62F have been found in males exposed to rivals [94]. The latter data are difficult to reconcile with the results of studies that quantify Sfps at the protein level, but may reflect the existence of important posttranscriptional regulation [97][98][99], or they may simply reflect strain differences, or differences in experimental design. In any case, males display modulation of Sfp production and transfer in response to perceived PCSS, which may represent an adaptive strategy to maximize reproductive returns from costly ejaculate investment and/or result from constraints imposed by resource limitation [100].…”
Section: (C) Quantitative Variation: Evolved and Plastic Allocation Omentioning
confidence: 99%